(untitled) - Polo, Russell (Hoboken, N.J., 2008)
The PC Hardware Essentials Project Manual offers a wealth of easy-to-read, practical, and up-to-date activities that reinforce fundamental PC hardware concepts. You will develop the core competencies and skills you'll need in the real world, including how to: Use System Properties to determine basic PC configuration, Remove and replace drives, drive cables, and expansion cards in a PC,...
Keywords: Microcomputers,Máy vi tính; Maintenance and repair,Bảo trì và sửa chữa